ANALYSIS OF PROMOTION INTENSITY LEVELS IN PAWNING AT PT. PEGADAIAN SYARIAH RENTENG PRAYA MARKET BRANCH - CENTRAL LOMBOK IN THE POST COVID - 19 PANDEMIC - Dewi Rispawati; Basuki Srihermanto; Iswan (Bajang Institute, 2022)
This research is entitled “Analysis of Promotion Intensity Level in Pawning at PT. Pegadaian Syariah Renteng Praya Market Branch, Central Lombok in the Middle of Post-Covid-19 Pandemic”. The purpose of this study was to determine the level of intensity of promotions carried out in pawning at PT. Pegadaian Syariah Renteng Praya Market Branch, Central Lombok In the Post Covid - 19 Pandemic, so that it can be seen the right promotion to be carried out in promoting pawning activities at PT. Pegadaian Syariah Renteng Praya Market Branch, Central Lombok in the Post Covid - 19 Pandemic. This type of research is a descriptive study with a case study method. In this study, data collection used using observation, interview and documentation techniques. The types of data used in this research are qualitative data and quantitative data. This study uses data sources, namely primary data and secondary data. Based on the results of the analysis, it is known that to find out what promotions can be done to increase the intensity of pawning at PT. Pegadaian Syariah Renteng Praya Market Branch Central Lombok in the Post Covid - 19 Pandemic period can be carried out such as: Personal Selling, Mass Selling, Sales Promotion, Public Relations, and Direct Marketing to achieve the goals of PT. Pegadaian Syariah Renteng Praya Market Branch Central Lombok in order to continue to exist and develop in the future